Empowering Sustainable Schools: The Impact of Eco-Green Assistance on Enhancing School Community Participation in the Adiwiyata Program - Dwi Cahaya Nurani; Windi Dwi Andika; Muhammad Khoirul Antony; Fahmi Surya Adikara; Ruri Tria Astika; Nabilah Mansur; Esti Susiloningsih; Muhammad Haekal Faiz; Cindy Putri Utami; Intan Putri Helisa (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2026)
The Adiwiyata program requires a structured service method to encourage sustainable environmental practices in schools. This community service activity aimed to enhance environmental awareness, improve waste management skills, and strengthen green school culture at SD Plus IGM Palembang. The program involved 31 participants, consisting of teachers and students, and applied a participatory service method through six stages: needs analysis, socialization, training, application of appropriate technology, mentoring, and evaluation. Needs analysis was conducted through observation and interviews to identify school conditions and environmental challenges. Training activities included hands-on demonstrations of biopore hole construction and guided implementation of a “Digital Waste Bank” application as an appropriate technology for waste management. Mentoring was carried out to ensure participants’ engagement and continuity of practice. Program evaluation employed a mixed-method approach using pre-test and post-test instruments to measure changes in participants’ knowledge, attitudes, and skills, supported by observation and interviews to assess behavioral changes and program effectiveness. The results showed an increase in participants’ competencies, with the average score improving from 74.68 to 96.6 and an N-Gain value of 0.90 (high category). The activity contributed to improved environmental awareness and more systematic waste management practices within the school environment. Tangible outputs included functional biopore holes and an operational Digital Waste Bank system. This service model supports the achievement of Sustainable Development Goals (SDGs) 4 and 13 and can be adopted by other schools in developing sustainable green school initiatives.